Incremental prognostic value of lung ultrasound on contemporary heart failure risk scores - Maestro-Benedicto, Alba; Rivas-Lasarte, Mercedes; Fernández-Martínez, Juan; López-López, Laura; Solé-González, Eduard; Brossa, Vicens; Mirabet, Sonia; Roig, Eulàlia; Cinca, Juan; Álvarez-García, Jesús; Sionis, Alessandro (Frontiers in Physiology, 2022)
Introduction: Over the last decades, several scores have been developed to aid clinicians in assessing prognosis in patients with heart failure (HF) based on clinical data, medications and, ultimately, biomarkers. Lung ultrasound (LUS) has emerged as a promising prognostic tool for patients when assessed at discharge after a HF hospitalization. We hypothesized that contemporary HF risk scores can be improved upon by the inclusion of the number of B-lines detected by LUS at discharge to predict death, urgent visit, or HF readmission at 6- month follow-up. Methods: We evaluated the discrimination improvement of adding the number of B-lines to 4 contemporary HF risk scores (Get with the Guidelines -GWTG-, MAGGIC, Redin-SCORE, and BCN Bio-HF) by comparing the change in the area under the receiver operating curve (AUC), the net reclassification index (NRI), and the integrated discrimination improvement (IDI).The population of the study was constituted by the 123 patients enrolled in the LUS-HF trial, adjusting the analyses by the intervention. Results: The AUC of the GWTG score increased from 0.682 to 0.789 (p = 0.02), resulting in a NRI of 0.608 and an IDI of 0.136 (p<0.05). Similar results were observed when adding the number of B-lines to the MAGGIC score, with an AUC that increased from 0.705 to 0.787 (p<0.05). This increase translated into a NRI of 0.608 and an IDI of 0.038 (p<0.05). Regarding Redin-SCORE at 1-month and 1-year, the AUC increased from 0.714 to 0.773 and from 0.681 to 0.757, although it did not reach statistical significance (p=0.08 and p=0.06 respectively). Both IDI and NRI were significantly improved (0.093 and 0.509 in the 1-month score, p<0.05; 0.056 and 0.111 in the 1-year score, p<0.05). Lastly, the AUC for the BCN Bio-HF score increased from 0.733 to 0.772, which was statistically non-significant, with a NRI value of 0.363 (p=0.06) and an IDI of 0.092 (p<0.05). Conclusions: Adding the results of LUS evaluated at discharge improved the predictive value of most of the contemporary HF risk scores. As it is a simple, fast, and non-invasive test it may be recommended to assess prognosis at discharge in HF patients.